Composite graphite material and preparation method thereof, secondary battery and device

By using an annular structure fragment cladding layer to coat graphite materials in secondary batteries, the weight loss rate is controlled, the problem of insufficient gram capacity of graphite materials is solved, the gram capacity and cycling performance of the battery are improved, the expansion rate is reduced, and the swelling rate is reduced. A comprehensive improvement in performance.

CN114245942BActive Publication Date: 2024-12-20CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN201980066188.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2019-12-03
Publication Date
2024-12-20
Estimated Expiration
2039-12-03

AI Technical Summary

Technical Problem

The actual gram capacity of graphite materials in existing secondary batteries is difficult to reach the theoretical value, and methods to increase the gram capacity usually affect other electrochemical properties.

Method used

The graphite material is coated with a cladding layer with an annular structural fragment. By controlling the weight loss rate of the composite graphite material from 0.1% to 0.55% when the temperature is raised from 40°C to 800°C in an inert non-oxidizing atmosphere, the weight loss rate of the composite graphite material is increased to improve the capacity and The expansion rate of the electrode sheet is reduced, and the composite graphite material with excellent properties is prepared by strictly controlling the cyclization and carbonization of the polymer.

Benefits of technology

It significantly improves the capacity and kinetic performance of the negative electrode active material, reduces the expansion rate of the negative electrode sheet, and improves the cycling performance of the battery, achieving the increase of the capacity close to the theoretical value, while maintaining the excellence of other electrochemical properties. sex.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114245942B_ABST
    Figure CN114245942B_ABST
Patent Text Reader

Abstract

The present application provides a composite graphite material and a preparation method thereof, a secondary battery and a device. The composite graphite material of the present application comprises a core material and a coating layer coated on at least a portion of the surface of the core material, wherein the core material comprises graphite, and the coating layer comprises a coating material having a ring structure fragment, wherein when the composite graphite material is heated from 40°C to 800°C in an inert non-oxidizing gas atmosphere, the weight loss rate of the composite graphite material is 0.1% to 0.55%. The composite graphite material of the present application can improve the gram capacity and reduce the pole piece expansion rate, and more preferably can also improve the cycle performance and dynamic performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of energy storage materials, in particular to the field of secondary batteries. Specifically, the present application relates to composite graphite materials and preparation methods thereof, secondary batteries and devices. Background Art

[0002] Secondary batteries have been widely used in various digital products, portable devices, electric vehicles, energy storage power supplies, etc. due to their advantages such as high energy density, long cycle life, safety and reliability, and no memory effect.

[0003] At present, carbonaceous materials are usually used as negative electrode active materials in commercially used secondary batteries. Among carbonaceous materials, graphite is widely used in secondary batteries due to its high theoretical gram capacity (372mA·h / g) and environmental friendliness. In actual products, the gram capacity of graphite materials is usually difficult to reach its theoretical gram capacity. Some existing methods for increasing the gram capacity of graphite materials often affect other electrochemical properties of the battery.

[0004] Therefore, there is an urgent need to provide a material with high gram capacity and other properties. Summary of the invention

[0005] The first aspect of the present application provides a composite graphite material, comprising a core material and a coating layer coated on at least a portion of the surface of the core material, wherein the core material comprises graphite, the coating layer comprises a coating material having a ring structure segment, and when the composite graphite material is heated from 40° C. to 800° C. in an inert non-oxidizing gas atmosphere, the weight loss rate of the composite graphite material is 0.1% to 0.55%. The composite graphite material of the present application can increase the gram capacity and reduce the pole piece expansion rate, and more preferably can also improve the cycle performance and / or dynamic performance of the battery.

[0006] A second aspect of the present application provides a method for preparing a composite graphite material, comprising the following steps:

[0007] (1) mixing a solution comprising a cyclizable polymer with graphite to obtain a slurry, wherein the mass ratio of the graphite to the cyclizable polymer is 30:1 to 400:1;

[0008] (2) drying the slurry to obtain powder;

[0009] (3) heat treating the powder at a temperature of 300 to 400° C. to obtain the composite graphite material;

[0010] The composite graphite material comprises a core material and a coating layer coated on at least a portion of the surface of the core material, the core material comprises graphite, and the coating layer comprises a coating material having annular structure fragments, wherein when the composite graphite material is heated from 40°C to 800°C in an inert non-oxidizing gas atmosphere, the weight loss rate of the composite graphite material is 0.1% to 0.55%.

[0011] A third aspect of the present application provides a secondary battery, comprising a negative electrode plate, wherein the negative electrode plate comprises a negative electrode active material, and the negative electrode active material comprises the composite graphite material described in the first aspect of the present application.

[0012] A fourth aspect of the present application provides a device, which includes the secondary battery provided by the third aspect of the present application.

[0013] The composite graphite material with the coating layer having the annular structure fragment of the present application not only improves the gram capacity of the negative electrode active material, but also reduces the expansion rate of the negative electrode pole piece containing the composite graphite material; further, when the battery is manufactured, the dynamic performance and / or cycle performance of the battery can be improved. In the method of the second aspect of the present application, the composite graphite material with the above-mentioned excellent performance is obtained by strictly controlling the degree of cyclization and carbonization of the polymer in the coating layer. This is unpredictable by those skilled in the art. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.

[0015] Figure 1 It is a schematic reaction formula for explaining the cyclization and partial carbonization of polyacrylonitrile.

[0016] Figure 2 It is the Raman spectra of the composite graphite materials of Example 2 and Comparative Example 1 of the present application.

[0017] Figure 3 TG diagram of the composite graphite material of Example 2 and Comparative Example 1 of the present application.

[0018] Figure 4 It is the infrared spectrum of a polymer material with a ring structure fragment.

[0019] Figure 5 It is a schematic diagram of a secondary battery provided in an embodiment of the present application.

[0020] Figure 6It is a schematic diagram of a battery module provided in an embodiment of the present application.

[0021] Figure 7 It is a schematic diagram of a battery pack provided in an embodiment of the present application.

[0022] Figure 8 yes Figure 7 Exploded view of the battery pack.

[0023] Fig. 9 It is a schematic diagram of a device provided in an embodiment of the present application.

[0024] Figure 10a-10b This is a SEM (scanning electron microscope) picture of the composite graphite material provided in the examples of the present application.

[0025] Fig.11 It is a schematic diagram of the structure of a composite graphite material provided in an embodiment of the present application.

[0026] The reference numerals are described as follows:

[0027] 1. Battery pack;

[0028] 2. Upper box;

[0029] 3. Lower box;

[0030] 4. Battery module;

[0031] 5. Secondary battery;

[0032] 10. Nuclear materials;

[0033] 20. Coating layer. DETAILED DESCRIPTION

[0034] In order to make the invention purpose, technical solution and beneficial technical effect of the present application clearer, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the embodiments described in this specification are only for explaining the present application, not for limiting the present application.

[0035] Where a composition is described as comprising or including specific components, it is contemplated that optional components not contemplated by the present invention are not excluded from the composition, and that the composition may consist of or be composed of the contemplated components; or where a method is described as comprising or including specific process steps, it is contemplated that optional process steps not contemplated by the present invention are not excluded from the method, and that the method may consist of or be composed of the contemplated process steps.

[0036] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined as its own lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unambiguous range.

[0037] In the description of this article, it should be noted that, unless otherwise specified, "above" and "below" are inclusive of the number itself, and "several" in "one or several" means two or more.

[0038] The terms "preferred" and "preferably" refer to embodiments of the present invention that may provide certain benefits under certain circumstances. However, other embodiments may also be preferred under the same or other circumstances. In addition, the recitation of one or more preferred embodiments does not mean that other embodiments are not useful, and is not intended to exclude other embodiments from the scope of the present invention.

[0039] The above-mentioned invention summary of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided through a series of embodiments. These embodiments can be used in various combinations, and the combined embodiments should be considered as specific embodiments or examples disclosed herein. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.

[0040] Coated graphite material

[0041] A first aspect of the present application provides a composite graphite material, comprising a core material and a coating layer coated on at least a portion of the surface of the core material, wherein the core material comprises graphite, the coating layer comprises a coating material having annular structure fragments, and when the composite graphite material is heated from 40°C to 800°C in an inert non-oxidizing gas atmosphere, the weight loss rate of the composite graphite material is 0.1% to 0.55%.

[0042] In some preferred embodiments, when the composite graphite material is heated from 40°C to 800°C in an inert non-oxidizing gas atmosphere, the weight loss rate of the composite graphite material is 0.1%-0.4%; more preferably 0.1%-0.3%. The inventors have found that when the weight loss rate of the composite graphite material is controlled within the given range, the composite graphite material has a higher gram capacity and the battery also has better cycle performance and anti-expansion performance. If the weight loss rate of the composite graphite material is less than 0.1%, the coating integrity of the coating layer on the surface of the graphite core material is greatly reduced, so that on the one hand, the effect of the coating layer itself on improving the gram capacity of the material is reduced; on the other hand, the effect between the coating layer and the binder is weakened, so that the bonding force and cohesion of the pole piece are low, and the expansion rate of the pole piece during the cycle becomes larger. The weight loss rate of the composite graphite material is greater than 0.55%, which will cause the material to consume too much active ions during the cycle, making the cycle performance of the battery cell worse; at the same time, the more active ions are consumed, the thicker the side reaction layer on the surface of the composite material is, and the pole piece will also expand.

[0043] In some embodiments, the inert non-oxidizing gas can be selected from one or more of nitrogen, carbon dioxide, ammonia, helium, and argon. In some preferred embodiments, nitrogen can be used as the inert non-oxidizing gas.

[0044] On the basis of the present application, those skilled in the art can reasonably determine the heating rate during the weight loss process. For example, the heating rate during the weight loss process can be 10°C / min or lower, preferably 5°C / min or lower. In an exemplary embodiment, the weight loss rate is measured in an inert non-oxidizing gas (e.g., nitrogen) atmosphere at a rate of 10°C / min from 40°C to 800°C.

[0045] In the composite graphite material of the present application, at least a portion of the surface of the core material is coated by a coating layer. In some preferred embodiments, the composite graphite material comprises a core material and a coating layer coated on at least 80% of the surface of the core material. More preferably, the composite graphite material comprises a core material and a coating layer coated on at least 90% of the surface of the core material. In some preferred embodiments, the composite graphite material comprises a core material and a coating layer coated on the surface of the core material.

[0046] In some embodiments, the coating layer includes a coating material having a nitrogen heterocyclic structure fragment, and at least part of the nitrogen heterocyclic structure has a carbon-nitrogen double bond. In this way, the hydrophilicity of the graphite material is greatly improved, and during the stirring process of the aqueous anode slurry, the composite graphite is more stably dispersed in the slurry, and the contact with the binder is more uniform, so the bonding force and cohesion of the pole piece are improved, thereby improving the cycle expansion performance of the battery.

[0047] The coating layer with the above-mentioned structural fragment itself can participate in the active ion deintercalation, and provide more active ion deintercalation channels, providing the graphite material with additional capacity other than the core, thereby increasing its gram capacity. This is unexpected by those skilled in the art, because in general, coating other coating layers (such as amorphous carbon coating layers, conventional polymer coating layers) on the surface of graphite materials will lead to a reduction in the effective active substances of the material, thereby reducing the gram capacity of the material. Moreover, considering the difficulty of further increasing the gram capacity as the gram capacity of the graphite material approaches the theoretical value, the coating modification of the present application shows more important significance and technological progress in the improvement of the gram capacity of the graphite material.

[0048] In addition, since the coating layer with the above structural fragments provides more channels suitable for active ion deintercalation, the active ion transmission efficiency of the material is improved. Moreover, the coating layer also has good electronic conductivity. Therefore, the graphite material has good kinetic characteristics, so that the kinetic performance and cycle performance of the battery using it are improved.

[0049] The nitrogen heterocyclic structure fragment may be a condensed ring or a non-condensed ring. In some preferred embodiments, the nitrogen heterocyclic structure fragment includes a nitrogen condensed ring structure fragment, wherein at least part of the nitrogen heterocyclic rings in the nitrogen condensed ring structure fragment have a carbon-nitrogen double bond.

[0050] In some embodiments, the nitrogen heterocyclic ring further has a carbon-carbon double bond. The conductivity of the coating layer is further improved.

[0051] In some embodiments, the nitrogen heterocycle is a five-membered ring or a six-membered ring. In this way, the coating layer has high elasticity and toughness, can better adapt to the expansion and contraction of repeated lithium extraction / insertion of the core, isolate the contact between the material surface and the electrolyte, reduce the capacity loss of the material due to electrolyte erosion, and thus improve the cycle performance of the battery.

[0052] In some embodiments, the nitrogen heterocyclic structure fragment may include one or more of a pyridine ring, an imidazole ring, a quinoline ring, and a pyrimidine ring. Preferably, the nitrogen heterocyclic structure fragment includes one or more nitrogen heterocyclic fused ring structure fragments in Formulas 1 to 3. Preferably, the nitrogen heterocyclic structure fragment includes a combination of at least two of Formulas 1 to 3. More preferably, the nitrogen heterocyclic structure fragment includes a combination of three of Formulas 1 to 3.

[0053]

[0054]

[0055] In some embodiments, the core material of the composite graphite material may be selected from one or more of artificial graphite and natural graphite.

[0056] In some preferred embodiments, when the core material is selected from artificial graphite, the composite graphite material can further improve the performance of the material when it also meets one or more of the following parameters.

[0057] In some embodiments, the D peak intensity I of the composite graphite material is D and G peak intensity I G The ratio I D / I G The D peak and the G peak are Raman characteristic peaks of graphite materials. The intensity of the D peak and the G peak can be measured using laser Raman spectroscopy, for example, using a LabRAM HR Evolution Raman spectrometer. In the Raman spectrum measured by the Raman spectrometer, the D peak is at 1300 cm -1 ~1400cm -1 The G peak is at 1550cm -1 Up to 1620cm -1 location.

[0058] In some embodiments, the composite graphite material I D / I G is 0.4 to 1.0. For example, the I D / I G It can be 0.4 to 0.95, 0.45 to 0.9, 0.5 to 0.8. D / I G When the graphite material is within the given range, the surface stability of the material can be further improved, thereby further reducing the volume expansion of the negative electrode during battery cycling. D / I G It is 0.5~0.8.

[0059] In some embodiments, when the composite graphite material has a compacted density (PD) of 1.6 g / cm 3 ~1.7g / cm 3 When the composite graphite material is in the pole piece, the orientation index OI value of the composite graphite material in the pole piece is ≤15, preferably 8-12.

[0060] When the composite graphite material is in a pole piece with a specific compaction density and the OI value is within the given range, the composite graphite material has a higher degree of isotropy, so that during the battery cycle, the expansion of the composite graphite material in the pole piece is dispersed in all directions, thereby further reducing the expansion of the pole piece during the cycle.

[0061] In this application, the orientation index OI value of the composite graphite material is defined as 004 / C 110In the X-ray diffraction analysis of the composite graphite material, the peak area of ​​the diffraction peak belonging to the (004) crystal plane is C 004 The peak area of ​​the diffraction peak attributed to the (110) crystal plane is C 110 .

[0062] X-ray diffraction analysis can refer to the standard JISK 0131-1996, using an X-ray diffractometer (such as Bruker D8 Discover X-ray diffractometer) for testing. X-ray diffraction analysis can refer to the standard JISK 0131-1996, using an X-ray diffractometer (such as Bruker D8 Discover X-ray diffractometer) for testing. In the X-ray diffraction analysis test, a copper target can be used as the anode target, and a Ni filter with a thickness of 0.02 mm can be used to filter the CuK β , CuK α The ray is the radiation source, and the wavelength of the ray is (Take K α1 and K α2 The scanning 2θ angle range was 20°~80° and the scanning rate was 4° / min.

[0063] An exemplary method for preparing a pole piece for testing the orientation index OI of the composite graphite material is as follows:

[0064] The composite graphite material of the present application, the binder styrene-butadiene rubber (SBR), the thickener sodium carboxymethyl cellulose (CMC-Na), and the conductive agent conductive carbon black (Super P) are dispersed in a solvent deionized water according to a mass ratio of 96.2:1.8:1.2:0.8, and mixed evenly to prepare a slurry; the slurry is evenly coated on the copper foil current collector, and the coating surface density can be 10 mg / cm 2 ~11mg / cm 2 (e.g. 10.5 mg / cm 2 ), the pole piece is dried and then cold pressed by a cold press, and the compaction density after cold pressing is 1.6g / cm 3 ~1.7g / cm 3 (e.g. 1.65 g / cm 3 The prepared pole piece is placed in an X-ray diffractometer, and the peak area C of the (004) crystal plane diffraction peak of the composite graphite material in the pole piece is obtained by X-ray diffraction analysis. 004 and the peak area C of the (110) crystal plane diffraction peak 110 , the orientation index OI value of composite graphite material = C 004 / C 110 .

[0065] In some embodiments, the Dv50 of the composite graphite material is 15 μm to 20 μm, preferably 15 μm to 18 μm.

[0066] Composite graphite material D v 50 is suitable for making it have higher active ion and electron transport performance, and can also reduce the side reaction of the electrolyte at the negative electrode. v 50% composite graphite material is also beneficial to improve its own powder compaction density.

[0067] In some embodiments, the volume average particle size D of the composite graphite material is v 10≥6μm. For example, D of composite graphite material v 10 can be 6 μm or more, 6.5 μm or more, 7 μm or more, or 7.5 μm or more. The artificial graphite has a smaller active specific surface area, which can further reduce the side reaction energy in the secondary battery. v 10 can be less than 11 μm, less than 10.5 μm, less than 10 μm, less than 9.5 μm, or less than 9 μm. Preferably, 6.5 μm≤D v 10≤10.5μm.

[0068] In some embodiments, the Dn10 of the composite graphite material is 1.0 μm to 3.0 μm, preferably 1.2 to 2.0 μm, and more preferably 1.3 to 1.8 μm. For example, the Dn10 of the composite graphite material may be about 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, or 1.8 μm.

[0069] Composite graphite material D n 10 is appropriate, then there are fewer side reactions between it and the electrolyte. In the negative electrode sheet prepared by the composite graphite material, the composite graphite material and additives such as binders can be evenly dispersed, and the overall bonding force of the electrode sheet is high. Therefore, the cycle performance and anti-expansion performance of the battery are further reduced. In particular, the D of the composite graphite material n 10 is appropriate, and it can also make itself have a higher gram capacity.

[0070] In the present application, the D of the composite graphite material n 10. D v 10. D v 50 can be measured with reference to standard GB / T19077.1-2016 using a laser particle size analyzer (such as Malvern Master Size 3000).

[0071] Among them, D n 10. D v 10. D vThe physical definition of 50 is as follows:

[0072] D n 10: The particle size corresponding to when the cumulative distribution percentage of the material reaches 10%;

[0073] D v 10: The particle size corresponding to when the cumulative volume distribution percentage of the material reaches 10%;

[0074] D v 50: The particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%.

[0075] In some embodiments, the specific surface area (SSA) of the composite graphite material is 0.5 m 2 / g~1.3m 2 / g, preferably 0.6m 2 / g~1.0m 2 / g.

[0076] The composite graphite material has an appropriate specific surface area, which can reduce the side reactions of the electrolyte on its surface and reduce the gas production, thereby reducing the volume expansion of the secondary battery during the cycle. At the same time, the composite graphite material can have a higher electrochemical reaction activity, so that the secondary battery has a higher dynamic performance, which is conducive to meeting the power requirements of the device. In addition, the appropriate specific surface area can also make the composite graphite material and the binder have a stronger bonding force, thereby improving the cohesion and bonding force of the pole piece, thereby further reducing the cyclic expansion of the pole piece.

[0077] The specific surface area can be tested by methods known in the art. For example, it can be tested by nitrogen adsorption specific surface area analysis test method according to GB / T 19587-2017, and calculated by BET (Brunauer Emmett Teller) method, wherein the nitrogen adsorption specific surface area analysis test can be performed by Tri-Star 3020 specific surface area pore size analysis tester of Micromeritics, USA.

[0078] In some embodiments, the composite graphite material has a compacted density of 1.80 g / cm2 measured under a pressure of 5 tons. 3 ~2.10g / cm 3 , preferably 1.93 g / cm 3 ~2.05g / cm 3 By adopting the compaction density of the above embodiment, the composite graphite material itself can have a higher gram capacity. The negative electrode sheet using the composite graphite material also has a higher compaction density, so that the battery has a higher energy density.

[0079] The compaction density of powder can be tested by methods known in the art. For example, GB / T 24533-2009 can be used to test using an electronic pressure testing machine (such as UTM7305): a certain amount of powder is placed on a special compaction mold, different pressures are set, the thickness of the powder under different pressures can be read on the equipment, and the compaction density under different pressures can be calculated.

[0080] In some embodiments, the tap density of the composite graphite material is 0.8 g / cm 3 ~1.15g / cm 3 , preferably 0.9 g / cm 3 ~1.05g / cm 3 . By adopting the composite graphite material with the tap density of the above embodiment, the negative electrode plate can have a suitable porosity, ensuring that the plate has good electrolyte wetting performance, so that the battery has a higher cycle performance. In addition, the tap density of the composite graphite material is conducive to obtaining a higher gram capacity. The compaction density of the negative electrode plate using the composite graphite material is also high, thereby improving the energy density of the battery.

[0081] The tap density of the composite graphite material can be tested by methods known in the art, for example, by referring to the standard GB / T5162-2006 and using a powder tap density tester (such as Dandong Better BT-301).

[0082] In some embodiments, the sulfur content of the composite graphite material is less than 0.02 wt%. The presence of sulfur in the coating layer may affect the stability of the above structural fragments, making it difficult to control the degree of cyclization and carbonization of the polymer in the coating layer. The sulfur content can be determined by elemental analysis.

[0083] The composite graphite material of the present application can be prepared by the method of the second aspect of the present application. Therefore, the present application also records the composite graphite material obtained by the method of the second aspect of the present application.

[0084] Method for preparing composite graphite material

[0085] A second aspect of the present application provides a method for preparing a composite graphite material, characterized in that it comprises the following steps:

[0086] (1) mixing a solution comprising a cyclizable polymer with a graphite core material to obtain a slurry, wherein the mass ratio of the graphite core material to the cyclizable polymer is 30:1 to 400:1;

[0087] (2) drying the slurry to obtain powder;

[0088] (3) Heat treating the powder at a temperature of 300 to 400° C. to obtain the composite graphite material.

[0089] The composite graphite material comprises a core material and a coating layer coated on at least a portion of the surface of the core material, wherein the core material comprises graphite, and the coating layer comprises a coating material having an annular structure segment. When the composite graphite material is heated from 40° C. to 800° C. in an inert non-oxidizing gas atmosphere, the weight loss rate of the composite graphite material is 0.1% to 0.55%.

[0090] The cladding layer may have the structure discussed above. Figure 4 FIG. 4 shows the infrared spectrum of the polymer material obtained after the above drying and heat treatment. Figure 4 The absorption peaks of carbon-nitrogen double bonds and carbon-carbon double bonds in the ring structure fragments can be clearly observed.

[0091] In some preferred embodiments, the coating layer comprises Specific examples of the coating layer include coating materials having one or more structural segments of the following formula: Preferably, the coating layer has at least two of the above structural fragments. More preferably, the coating layer has at least two of the above structural fragments. Even more preferably, the coating layer has a combination of the above structural fragments.

[0092] The graphite core material in step (1) can be obtained commercially.

[0093] The content of the coating layer in the composite graphite can be controlled by adjusting the amount of polymer added. The degree of cyclization and carbonization of the polymer can be controlled by adjusting the temperature and time of the heat treatment step. Through a large number of experiments, the inventors of the present application have found the preferred amount of raw materials, the temperature and time of the heat treatment step. The advantages of adjusting the content of the coating layer within a certain range are discussed above and will not be repeated here.

[0094] In some preferred embodiments, the mass ratio of graphite to cyclizable polymer is m G ∶m P is 40:1 to 200:1, more preferably 50:1 to 150:1. For example, the mass ratio of graphite to the cyclizable polymer is m G ∶m P The mass ratio of graphite to the cyclizable polymer may be 70:1 to 120:1, more preferably 80:1 to 110:1. G ∶m P It is 100:1.

[0095] In some preferred embodiments, in step (1), the cyclizable polymer includes polyacrylonitrile (PAN) or a copolymer thereof. Preferably, the cyclizable polymer includes a copolymer of polyacrylonitrile or acrylonitrile and olefins. More preferably, the cyclizable polymer includes a copolymer of polyacrylonitrile or acrylonitrile and acrylic acid, acrylamide, and itaconic acid monomers. For example, the cyclizable polymer includes a copolymer of polyacrylonitrile or acrylonitrile and one or more of itaconic acid (IA), vinyl acetate (Vac), acrylic acid (AA), methyl acrylate (MA) and acrylamide (AM). Particularly preferably, the cyclizable polymer is or includes polyacrylonitrile.

[0096] In some embodiments, the number average molecular weight of the cyclizable polymer is 50,000 to 150,000 Da, preferably 80,000 to 120,000 Da.

[0097] In some embodiments, in step (1), the solution comprising a cyclizable polymer may include one or more of water, N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide. More preferably, the solution comprising a cyclizable polymer may be or include N-dimethylformamide.

[0098] The solution comprising a cyclizable polymer in step (1) can be obtained by methods known in the art. For example, the solution comprising a cyclizable polymer can be obtained by dissolving the cyclizable polymer in a solvent and stirring until dissolved.

[0099] The slurry containing the cyclizable polymer can be dried by methods known in the art. For example, the drying method includes but is not limited to spray drying, flash evaporation, rotary evaporation, freeze drying, etc. In some embodiments, in step (2), spray drying is used. The drying temperature can be adjusted according to the solvent used for the solution or slurry. Preferably, in step (2), the drying is spray drying carried out at 180 to 210°C. More preferably, the drying is spray drying carried out at 190 to 205°C.

[0100] In some embodiments, in step (3), the heat treatment is performed in an inert non-oxidizing gas. Examples of inert non-oxidizing gases include, but are not limited to, nitrogen, carbon dioxide, ammonia, and inert gases (e.g., helium, argon), and combinations thereof. In some preferred embodiments, nitrogen can be used as the inert non-oxidizing gas.

[0101] In some embodiments, in step (3), the heat treatment is carried out at a temperature of 350°C to 400°C. In the heat treatment process of the cyclizable polymer (especially polyacrylonitrile), the temperature of the heat treatment has a key influence on the cyclization and carbonization of the polymer. A large number of studies have found that when the heat treatment is carried out at a temperature of 200°C or lower, the polymer coating has not yet been thermally cracked and is still in a polymer state. The polymer itself has no gram capacity, so the gram capacity of the coated material is reduced. When the temperature rises from 300°C to 400°C, as the temperature rises, the coating begins to decompose, the gram capacity of the material increases, and the anti-expansion performance is also improved to the maximum extent. As the temperature further increases, for example, when the heat treatment is carried out at a temperature of 500°C or higher, the disorder of the coating itself after the polymer decomposition decreases, and it cannot improve the cyclic expansion problem of the pole piece. Therefore, the degree of polymer cyclization and carbonization can be adjusted by strictly controlling the temperature of the heat treatment. By controlling the temperature of the above-mentioned preferred heat treatment, it is possible to better control the partial carbonization of the cyclizable polymer (especially polyacrylonitrile) while maintaining the cyclic structure fragments discussed above.

[0102] In some embodiments, in step (3), the heat treatment time is 3 to 6 hours; preferably, the heat treatment time is 3.5 to 5 hours. By adopting the above preferred heat treatment time, the carbonization process of the cyclizable polymer (especially polyacrylonitrile) can be controlled so that the coating layer has the cyclic structure fragment discussed above.

[0103] During the heat treatment, the cyclizable polymer (especially polyacrylonitrile) gradually dehydrogenates and cyclizes to form a ring structure, and releases small molecules such as NH3 and HCN. The C≡N bond gradually disappears, forming a ring structure fragment. Figure 1 The schematic reaction formula of polyacrylonitrile cyclization and partial carbonization is shown in FIG. Generally speaking, it can be considered that polyacrylonitrile mainly undergoes intramolecular cyclization below 220°C (e.g. Figure 1 (a)), and intermolecular cyclization occurs at about 300 °C (as shown in Figure 1 (as shown in (b)).

[0104] When the heat treatment temperature reaches about 350°C or even 400°C, the cyclic structure fragments begin to be partially carbonized to form cyclic structure fragments with carbon-nitrogen double bonds and carbon-carbon double bonds, or with Moreover, as the carbonization proceeds, a coating material having one or more structural fragments of the following formula is formed:

[0105] It is worth noting that the carbonization process also affects the weight loss rate of the composite graphite material in the process from 40°C to 800°C in an inert non-oxidizing gas atmosphere. If the degree of carbonization is too high, most of the cyclic structure fragments are decomposed, and the weight loss rate of the obtained composite graphite material is significantly reduced. For example, when the carbonization process is carried out at 1000°C for 4 hours, the weight loss rate of the obtained composite graphite material in the process from 40°C to 800°C is extremely small, indicating that most (even almost all) of the cyclizable polymers in the coating layer are converted into amorphous carbon, which reduces the gram capacity and reduces the anti-expansion performance of the battery. If the degree of carbonization is too low, the cyclizable polymer (especially polyacrylonitrile) still retains a large amount of cyclic structure, and no sufficient carbonization decomposition occurs, then the weight loss rate of the obtained composite graphite material in the process from 40°C to 800°C increases, and the obtained composite graphite material has very limited improvement on the performance of the battery, such as insufficient kinetic performance of the battery, reduced maximum charge rate, or slight lithium precipitation.

[0106] In some preferred embodiments, the graphite core material in step (1) can also be prepared by the following steps:

[0107] S10, crushing the raw coke materials and performing graded treatment.

[0108] S20, shaping the product obtained in step S10.

[0109] S30, granulating the product obtained in step S20, wherein the amount of binder added in the granulation process does not exceed 5% of the total weight of the raw coke material.

[0110] S40, graphitizing the product obtained in step S30 at a temperature of 2800° C. to 3200° C. to obtain the graphite.

[0111] In the above preparation method, the graphite is artificial graphite.

[0112] In the above preparation method, in step S10, the raw coke material can be selected from one or more of raw petroleum coke and raw asphalt coke, preferably raw petroleum coke.

[0113] Preferably, the raw coke material is non-needle coke. The non-needle coke can be selected from one or more of non-needle green petroleum coke and non-needle green asphalt coke. Preferably, the non-needle coke includes non-needle green petroleum coke.

[0114] In some embodiments, in step S10, preferably, the volatile matter content of the coke-forming raw material is 6% to 12% (weight percentage); preferably, the volatile matter content of the coke-forming raw material is 7% to 10%.

[0115] The coke raw material has an appropriate volatile matter content, which can make it have high self-adhesiveness during the granulation process in step S20, improve the bonding strength between primary particles in the graphite, and make the artificial graphite have high structural strength and high gram capacity.

[0116] In some embodiments, the sulfur content of the raw coke material may be less than 2%, less than 1.5%, less than 1%, or less than 0.5%. The raw coke material has a lower sulfur content, which can prevent the increase in the specific surface area of ​​the graphite material caused by the escape of more sulfur components in the subsequent process. Preferably, the sulfur content of the raw coke material is ≤1%.

[0117] In some embodiments, step S20 further includes removing fine powder after shaping. n 10 is within an appropriate range so that the D of the obtained artificial graphite n 10 is within the required range.

[0118] A large number of studies have shown that the post-shaping fine powder removal process in step S20 is beneficial for further improving the gram capacity of artificial graphite.

[0119] In step S30, preferably, the granulation process is carried out without adding a binder. When the amount of binder is controlled within the given range, the gram capacity of graphite can be further improved; in particular, in the absence of a binder, the self-adhesiveness of raw coke is utilized to granulate it, which can improve the overall structural strength of the artificial graphite particles. When the artificial graphite is used as the core of the graphite material of the present application, the corresponding properties of the graphite material are also improved. Preferably, when the volatile content of the raw coke material is above 7%, the step S30 can granulate the granular product obtained in step S20 without adding a binder. However, the volatile content of the raw coke material should not be too high, otherwise it will significantly reduce the gram capacity of the graphite and affect its processing performance during subsequent use.

[0120] Furthermore, by adjusting the above process conditions, the volume average particle size D of the granulated product can be adjusted. v 50 is within the required range, or the D of the granulated product is v 10. D v 50 and D v 90 are all within the required range.

[0121] By adjusting the particle size distribution of step S10 and / or S30, the D of the final composite graphite material can be v 50. D v 10 is within the required range. By regulating the particle size distribution of graphite within an appropriate range, it is also beneficial to obtain an appropriate tap density and powder compaction density.

[0122] In some preferred embodiments, the temperature of the graphitization treatment in step S40 is 2900°C to 3100°C.

[0123] Secondary battery

[0124] The third aspect of the present application provides a secondary battery, comprising a negative electrode plate, wherein the negative electrode plate comprises a negative electrode active material, characterized in that the negative electrode active material comprises the composite graphite material described in the first aspect of the present application.

[0125] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode membrane disposed on at least one surface of the negative electrode current collector and including a negative electrode active material, and the negative electrode active material includes the composite graphite material described in the first aspect of the present application.

[0126] Due to the use of the composite graphite material of the first aspect of the present application, the secondary battery of the present application has a higher energy density and excellent anti-expansion performance, thereby enabling the battery to have both a higher energy density and better cycle performance.

[0127] In some embodiments, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film is laminated on any one or both of the two opposite surfaces of the negative electrode current collector. The negative electrode current collector may be made of a material having good electrical conductivity and mechanical strength. In some embodiments, the negative electrode current collector is made of copper foil.

[0128] In some embodiments, the negative electrode film may also optionally include other negative electrode active materials that can be used for the negative electrode of a secondary battery. The other negative electrode active materials may be one or more of other graphite materials, mesophase microcarbon beads (abbreviated as MCMB), hard carbon and soft carbon.

[0129] In some embodiments, the negative electrode film further comprises a binder. As an example, the binder can be selected from one or more of polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0130] In some embodiments, the negative electrode membrane may further include a thickener. As an example, the thickener may be sodium carboxymethyl cellulose (CMC-Na).

[0131] In some embodiments, the negative electrode film may further include a conductive agent. As an example, the conductive agent for the negative electrode film may be selected from one or more of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0132] The secondary battery may also include a positive electrode sheet. During the battery charging and discharging process, active ions are inserted and removed back and forth between the positive electrode sheet and the negative electrode sheet. In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode membrane disposed on at least one surface of the positive electrode current collector and including a positive electrode active material.

[0133] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film is laminated on any one or both of the two opposite surfaces of the positive electrode current collector. The positive electrode current collector may be made of a material having good electrical conductivity and mechanical strength. In some embodiments, the positive electrode current collector may be aluminum foil.

[0134] The positive electrode sheet may include a positive electrode active material. The present application does not specifically limit the specific type of the positive electrode active material, and materials known in the art that can be used for the positive electrode of a secondary battery may be used, and those skilled in the art may select according to actual needs.

[0135] In some embodiments, the positive electrode active material may be selected from one or more of lithium transition metal oxides and modified compounds thereof. The modified compound may be a lithium transition metal oxide that is doped and / or coated. For example, the lithium transition metal oxide may be selected from one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium phosphates containing an olivine structure. Preferably, the positive electrode active material includes one or more of lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide.

[0136] As an example, the positive electrode active material of the secondary battery can be selected from LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.85 Co 0.15 Al 0.05 One or more of O2, LiFePO4 (LFP) and LiMnPO4.

[0137] In some embodiments, the positive electrode membrane may also optionally include a binder. The type of the binder is not specifically limited, and those skilled in the art may select it according to actual needs. As an example, the binder for the positive electrode membrane may include one or more of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE).

[0138] In some embodiments, the positive electrode film may further include a conductive agent. There is no specific limitation on the type of the conductive agent, and those skilled in the art may select the conductive agent according to actual needs. As an example, the conductive agent used for the positive electrode film may include one or more of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0139] The secondary battery also includes an electrolyte. The electrolyte plays a role in conducting ions between the positive electrode plate and the negative electrode plate. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (i.e., an electrolyte).

[0140] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0141] In some embodiments, the electrolyte salt can be selected from one or more of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalatoborate), LiBOB (lithium dioxalatoborate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorobis(oxalatophosphate)) and LiTFOP (lithium tetrafluorooxalatophosphate).

[0142] In some embodiments, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0143] In some embodiments, the electrolyte may also optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, additives that improve battery low temperature performance, etc.

[0144] Secondary batteries using electrolytes and some secondary batteries using solid electrolytes also include a separator. The separator is arranged between the positive electrode plate and the negative electrode plate to play a role of isolation. The present application has no particular restrictions on the type of separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected. In some embodiments, the material of the separator can be selected from one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer can be the same or different.

[0145] Some embodiments of the present application also provide a method for preparing a secondary battery, which includes the step of preparing a negative electrode plate using any one or more of the composite graphite materials of the present application.

[0146] In some embodiments, the step of preparing a negative electrode sheet using the composite graphite material of the present application may include: dispersing the negative electrode active material including the composite graphite material of the first aspect of the present application and a binder, as well as an optional thickener and a conductive agent in a solvent, the solvent may be deionized water, to form a uniform negative electrode slurry; coating the negative electrode slurry on the negative electrode collector, and obtaining a negative electrode sheet after drying, cold pressing and other processes.

[0147] The method for preparing a secondary battery may further include the step of preparing a positive electrode sheet. In some embodiments, the positive electrode active material, the conductive agent and the binder may be dispersed in a solvent (e.g., N-methylpyrrolidone, referred to as NMP) to form a uniform positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, a positive electrode sheet is obtained.

[0148] The method for preparing a secondary battery also includes the step of assembling a negative electrode sheet, a positive electrode sheet and an electrolyte to form a secondary battery. In some embodiments, the positive electrode sheet, the separator and the negative electrode sheet can be wound or stacked in sequence, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, thereby obtaining a battery cell; the battery cell is placed in an outer package, and the electrolyte is injected and sealed to obtain the secondary battery of the present application.

[0149] In some embodiments, the secondary battery may be a lithium ion secondary battery.

[0150] In some embodiments, the secondary battery may include an outer package and a battery cell encapsulated in the outer package. The number of battery cells in the secondary battery may be one or more, which may be adjusted according to demand.

[0151] In some embodiments, the outer packaging of the secondary battery can be a soft package (e.g., a bag, the material of which can be plastic, such as one or more of polypropylene PP, polybutylene terephthalate PBT, polybutylene succinate PBS, etc.), or a hard shell (e.g., an aluminum shell, etc.).

[0152] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 5 The secondary battery 5 is a square structure as an example.

[0153] In some embodiments, secondary batteries may be assembled into a battery module. The battery module may contain multiple secondary batteries, and the specific number may be adjusted according to the application and capacity of the battery module.

[0154] Figure 6 A battery module 4 is shown as an example. Figure 6 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0155] Optionally, the battery module 4 may further include a housing having a housing space, and the plurality of secondary batteries 5 are housed in the housing space.

[0156] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0157] Figure 7 and Figure 8 A battery pack 1 is shown as an example. Figure 7 and Figure 8 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0158] Device

[0159] The fourth aspect of the present application provides a device. The device includes the secondary battery of the third aspect of the present application. The secondary battery can be used as a power source or energy storage device for the device. The device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0160] The device can select a secondary battery, a battery module or a battery pack according to its usage requirements.

[0161] Fig. 9 The device is used as an example. The device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module can be used.

[0162] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0163] Example

[0164] The following examples more specifically describe the disclosure of the present application, which are intended for illustrative purposes only, as it will be apparent to those skilled in the art that various modifications and variations are possible within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0165] The nuclear materials used in the following examples of this application can be obtained commercially or according to the following preparation method:

[0166] (1) Preparation of artificial graphite A: non-acicular green petroleum coke (volatile matter of about 9.5%, sulfur content of about 0.5%) is used as raw material, which is crushed and then graded; the granular product obtained after crushing is shaped; the granular product obtained after shaping is added to the reactor of a granulator, and the green petroleum coke raw material is granulated without adding a binder; and then graphitized at a temperature of about 3000° C. to obtain artificial graphite A.

[0167] (2) Preparation of artificial graphite B: needle-shaped cooked petroleum coke is used as raw material, which is crushed and then graded; granulation is performed using asphalt as a binder, and the amount of asphalt accounts for 8% of the total weight of the raw material; and then graphitization is performed at a temperature of about 2900°C to obtain artificial graphite B.

[0168] Example 1

[0169] Preparation of composite graphite materials

[0170] 1) providing a solution including a cyclizable polymer: dissolving polyacrylonitrile in a solvent, N-dimethylformamide, and stirring until the polymer is completely dissolved;

[0171] 2) adding artificial graphite A to the polymer solution obtained in step 1, stirring and mixing evenly to obtain a mixed slurry;

[0172] 3) The mixed slurry obtained in step 2 is transferred to a spray drying device by a peristaltic pump and dried in a nitrogen atmosphere to obtain a dry powder, wherein the peristaltic pump speed is 20 rpm and the spray drying temperature range is 190° C.;

[0173] 4) The dried powder obtained in step 3 is heat-treated in a nitrogen atmosphere at a temperature of 400° C. for 4 h to obtain a composite graphite material.

[0174] Preparation of negative electrode

[0175] The composite graphite material, conductive agent Super P, binder styrene-butadiene rubber (SBR), and thickener CMC-Na prepared above were fully stirred and mixed in a proper amount of deionized water at a mass ratio of 96.2:0.8:1.8:1.2 to form a uniform negative electrode slurry; the negative electrode slurry was coated on the surface of the negative electrode current collector copper foil, and after drying and cold pressing, a negative electrode sheet was obtained. The compaction density of the negative electrode sheet is 1.65g / cm 3 , surface density is 10.7mg / cm 2 .

[0176] Preparation of positive electrode

[0177] The positive electrode active material LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523), conductive agent Super-P, and adhesive polyvinylidene fluoride (PVDF) are dissolved in a solvent N-methylpyrrolidone (NMP) in a weight ratio of 96:2:2 and mixed evenly to form a positive electrode slurry. The positive electrode slurry is then evenly coated on the current collector aluminum foil. After drying and cold pressing, the positive electrode sheet is obtained.

[0178] Preparation of electrolyte

[0179] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1, and then LiPF6 is uniformly dissolved in the above solution to obtain an electrolyte, wherein the concentration of LiPF6 is 1 mol / L.

[0180] Isolation film

[0181] Polyethylene (PE) film is used.

[0182] Preparation of secondary batteries

[0183] The positive electrode sheet, separator and negative electrode sheet are stacked in order, and a battery cell is obtained after winding. The battery cell is placed in an outer package, and the electrolyte is added. After packaging, standing, forming, aging and other processes, a secondary battery is obtained.

[0184] Examples 2-11 and Comparative Examples 1-8

[0185] In Examples 2-11 and Comparative Examples 1-8, a preparation method similar to that of Example 1 was adopted, and the differences are detailed in Table 1.

[0186] Test Section

[0187] (1) Thermal gravimetric loss (TG)

[0188] The negative electrode active materials in each embodiment and comparative example were measured using a STA449F3 model synchronous thermal analyzer. The atmosphere was nitrogen, the test temperature range was 40°C to 800°C, and the heating rate was 10°C / min. The mass percentage of the material mass measured at different temperatures relative to the initial material mass was recorded.

[0189] (3) Gram capacity

[0190] The prepared composite graphite material, conductive agent Super P, binder (PVDF) and solvent NMP (N-methylpyrrolidone) are mixed evenly in a mass ratio of 91.6:1.8:6.6 to make a slurry, and the prepared slurry is coated on a copper foil current collector, dried in an oven and set aside; a metal lithium sheet is used as a counter electrode; a polyethylene (PE) film is used as an isolation membrane; ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1, and then LiPF6 is evenly dissolved in the above solution to obtain an electrolyte, wherein the concentration of LiPF6 is 1 mol / L; the above parts are assembled into a CR2430 button battery in an argon-protected glove box.

[0191] After the button cell was left to stand for 12 hours, it was discharged at a constant current of 0.05C to 0.005V, left to stand for 10 minutes, and then discharged at a constant current of 50μA to 0.005V, left to stand for 10 minutes, and then discharged at a constant current of 10μA to 0.005V; then it was charged at a constant current of 0.1C to 2V, and the charging capacity was recorded. The ratio of the charging capacity to the mass of the composite graphite material is the gram capacity of the prepared artificial graphite.

[0192] The button cell can be tested using a LAND CT2001A battery testing system to calculate the gram capacity of the composite graphite material.

[0193] (4) Cycle performance

[0194] At 25°C, the lithium-ion secondary battery is charged to 4.3V at a constant current rate of 1C, then charged at a constant voltage until the current is less than or equal to 0.05C, and then discharged to 2.8V at a constant current rate of 1C. This is a charge and discharge cycle, and the discharge capacity of this time is the discharge capacity of the first cycle. The lithium-ion secondary battery is charged and discharged 1400 times according to the above method, and the discharge capacity of the 1400th cycle is recorded. The capacity retention rate of the lithium-ion secondary battery after 1400 1C / 1C cycles is calculated.

[0195] Capacity retention rate (%) of lithium ion secondary battery after 1400 1C / 1C cycles = discharge capacity at 1400th cycle / discharge capacity at 1st cycle×100%.

[0196] (5) Negative electrode expansion rate test

[0197] The thickness of the negative electrode after cold pressing is recorded as H0. The cold pressed negative electrode, positive electrode, separator and electrolyte are made into a secondary battery. At 25°C, the secondary battery is subjected to a 1C / 1C cycle of 100% DOD (100% depth of discharge, that is, full charge and then full discharge) in a Xinwei charger and discharge machine. A full charge and discharge cycle is recorded as one circle, and the cycle stops when it reaches 1400 circles. Then charge the secondary battery to 100% SOC (State of Charge), disassemble the secondary battery and test the thickness of the corresponding negative electrode, which is recorded as H1. The cyclic expansion rate of the negative electrode is: (H1 / H0-1)×100%.

[0198] (6) Dynamic performance

[0199] At 25°C, the batteries prepared in the examples and comparative examples were fully charged at x C and fully discharged at 1 C for 10 times, and then the batteries were fully charged at x C again, and then the negative electrode plates were disassembled and the lithium deposition on the surface of the negative electrode plates was observed. If no lithium deposition was observed on the negative electrode surface, the charging rate x C was increased by 0.1 C as a gradient and tested again until lithium deposition was observed on the negative electrode surface, and the test was stopped. The charging rate (x-0.1) C at this time was the maximum charging rate of the battery.

[0200] Other parameters of the composite graphite material were tested according to the test methods described above.

[0201]

[0202] Comparing Comparative Example 1 with Examples 1-5 and Comparative Example 2 with Example 11, it can be seen that by coating the graphite surface with a coating material having a specific structure, the gram capacity and anti-expansion performance can be significantly improved at the same time. Comparing Comparative Examples 3-4 with Examples 1-5, it can be seen that under the same heat treatment conditions, by controlling the mass ratio of graphite to the cyclizable polymer and adjusting the weight loss rate of the composite graphite material, a higher gram capacity and excellent anti-expansion performance can be obtained. In Comparative Example 4, when the coating is too much, the coating layer consumes too much active lithium, the active lithium loss is large, and the cycle becomes poor.

[0203] Comparing Comparative Example 7 with Example 4, it can be seen that compared with the polymer-coated graphite material that has not been carbonized, the partially carbonized composite graphite material can significantly improve the gram capacity, and significantly improve the cycle performance and anti-expansion performance of the battery. Comparing Comparative Example 5 with Example 4, it can be seen that when the heat treatment temperature reaches 1000°C, the carbonization degree is too high, the desired annular structure fragments in the coating layer are gradually destroyed, the gram capacity is reduced, and the expansion rate is significantly increased.

[0204] Comparing Comparative Examples 1 and 8 with Example 4, it can be seen that, compared with conventional coating materials, when polyacrylonitrile is used as the cyclizable polymer, the gram capacity is significantly increased and the anti-swelling performance is effectively improved.

[0205] In addition to the effects of coating materials and carbonization degree on battery performance discussed above, the inventors surprisingly found that when the core material is artificial graphite A, the expansion rate of the pole piece in the battery is significantly reduced, and the cycle performance of the battery is improved. This can be confirmed by comparing Example 4 with Example 11.

[0206] like Figure 2 As shown, the D peak intensity I of the composite graphite of Example 2 D and G peak intensity I G The ratio I D / I GThe peak intensity of D in Comparative Example 1 is 0.82, which is within the range of 0.4 to 1.0. D and G peak intensity I G The ratio I D / I G is 0.21, which is not within the range of 0.4 to 1.0. Among them, the D peak is at 1300 cm -1 ~1400cm -1 The G peak is at 1550cm -1 Up to 1620cm -1 location.

[0207] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. A composite graphite material, comprising a core material and a coating layer covering at least a portion of the surface of the core material, characterized in that: The core material is graphite, the coating layer includes a coating material having a ring structure segment, the precursor of the coating material is one or more of polyacrylonitrile or its copolymers, and the ring structure segment is one or more of Formula 1 to Formula 3: , When the composite graphite material is heated from 40° C. to 800° C. at a heating rate of 10° C. / min or less in an inert non-oxidizing gas atmosphere, the weight loss rate of the composite graphite material is 0.13% to 0.53%.

2. The composite graphite material according to claim 1, characterized in that: When the temperature of the composite graphite material is increased from 40° C. to 800° C. in an inert non-oxidizing gas atmosphere, the weight loss rate of the composite graphite material is 0.13%-0.4%.

3. The composite graphite material according to claim 1, characterized in that When the temperature of the composite graphite material is increased from 40° C. to 800° C. in an inert non-oxidizing gas atmosphere, the weight loss rate of the composite graphite material is 0.13%-0.3%.

4. The composite graphite material according to any one of claims 1 to 3, characterized in that: The core material is artificial graphite.

5. The composite graphite material according to claim 4, characterized in that: The D peak intensity I of the composite graphite material D and G peak intensity I G The ratio I D / I G It is 0.4~1.

0.

6. The composite graphite material according to claim 4, characterized in that: The D peak intensity I of the composite graphite material D and G peak intensity I G The ratio I D / I G It is 0.5~0.

8.

7. The composite graphite material according to claim 4, characterized in that The composite graphite material satisfies: when the compacted density of the composite graphite material is 1.6 g / cm 3 ~ 1.7g / cm 3 When the electrode is in the electrode, the peak area C of the (004) crystal plane of the composite graphite material 004 The peak area C of (110) crystal plane 110 Ratio C 004 / C 110 ≤15.

8. The composite graphite material according to claim 4, characterized in that The composite graphite material satisfies: when the compacted density of the composite graphite material is 1.6 g / cm 3 ~ 1.7g / cm 3 When the electrode is in the electrode, the peak area C of the (004) crystal plane of the composite graphite material 004 The peak area C of (110) crystal plane 110 The ratio is 8≤C 004 / C 110 ≤12.

9. The composite graphite material according to claim 4, characterized in that The composite graphite material also satisfies one or more of the following (1) to (6): (1) The Dv50 of the composite graphite material is 15 μm to 20 μm; (2) The Dv10 of the composite graphite material is ≥6 μm; (3) The Dn10 of the composite graphite material is 1.0 μm to 3.0 μm; (4) The specific surface area of ​​the composite graphite material is 0.5 m 2 / g~1.2m 2 / g; (5) The compacted density measured under a pressure of 5 tons is 1.80 g / cm 3 ~2.10 g / cm 3 ;as well as (6) The tap density of the composite graphite material is 0.8 g / cm 3 ~1.15 g / cm 3 .

10. The composite graphite material according to claim 4, characterized in that The composite graphite material also satisfies one or more of the following (1) to (6): (1) The Dv50 of the composite graphite material is 15 μm to 18 μm; (2) The Dv10 of the composite graphite material is 6.5 μm ≤ D v 10 ≤10.5μm; (3) The Dn10 of the composite graphite material is 1.2 μm to 2.0 μm; (4) The specific surface area of ​​the composite graphite material is 0.6 m 2 / g~1.0m 2 / g; (5) The compacted density measured under a pressure of 5 tons is 1.93 g / cm 3 ~2.05 g / cm 3 ;as well as (6) The tap density of the composite graphite material is 0.9 g / cm 3 ~1.05 g / cm 3 .

11. The composite graphite material according to any one of claims 1 to 3, characterized in that: The sulfur content of the composite graphite material is less than 0.02 wt %.

12. A method for preparing a composite graphite material according to any one of claims 1 to 11, characterized in that: The following steps are involved: (1) mixing a solution comprising a cyclizable polymer with a graphite core material to obtain a slurry, wherein the mass ratio of the graphite core material to the cyclizable polymer is 30:1 to 400:1; (2) drying the slurry to obtain powder; (3) heat-treating the powder at a temperature of 350-400° C. to obtain the composite graphite material, wherein the heat-treating time is 3-6 hours.

13. The method according to claim 12, characterized in that The mass ratio m of the graphite core material to the cyclizable polymer G :m P It is 40:1~200:

1.

14. The method according to claim 12, characterized in that The mass ratio m of the graphite core material to the cyclizable polymer G :m P It is 50:1~150:

1.

15. The method according to any one of claims 12 to 14, characterized in that: The cyclizable polymer is one or more of polyacrylonitrile or its copolymers.

16. The method according to any one of claims 12 to 14, characterized in that: The cyclizable polymer is polyacrylonitrile.

17. The method according to any one of claims 12 to 14, characterized in that The number average molecular weight of the cyclizable polymer is 50,000 to 150,000 Da.

18. The method according to any one of claims 12 to 14, characterized in that The number average molecular weight of the cyclizable polymer is 80,000 to 120,000 Da.

19. The method according to claim 12, characterized in that In step (3), the heat treatment time is 3.5 to 5 hours.

20. A secondary battery, comprising a negative electrode plate, wherein the negative electrode plate comprises a negative electrode active material, characterized in that: The negative electrode active material comprises the composite graphite material according to any one of claims 1 to 11.

21. A device, characterized in that: The device comprises the secondary battery according to claim 20.